2004
DOI: 10.1590/s0102-311x2004000700010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da validação das informações de peso e estatura em gestantes atendidas em maternidades municipais no Rio de Janeiro, Brasil

Abstract: Os objetivos principais deste artigo são a avaliação da concordância entre as informações de peso e estatura medidas e referidas, bem como a identificação das principais características de 150 gestantes que souberam ou não referir seu peso anterior, peso final e estatura. Os resultados evidenciam que as informações referidas para o peso anterior aproximam-se dos valores medidos (coeficiente de correlação de Pearson (0,96) e intraclasse (0,92); p < 0,05), o mesmo ocorrendo em relação à variável peso final (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
4
10
2
6
Order By: Relevance
“…Another possible limitation was the imputation of values for weights at the end of pregnancy in 19.1% of the sample, although the proportion of the sample in which imputation was used was lower than that used in another study (24.5%) that applied the same methodology 35 . Reported pre-pregnancy weight was also used, which was supported by a strong correlation with measured weight, shown in previous studies on Brazilian pregnant women (r = 0.92) 36 . Finally, different sources of secondary data were used, collected from official records to obtain information regarding the prenatal period.…”
Section: Discussionmentioning
confidence: 81%
“…Another possible limitation was the imputation of values for weights at the end of pregnancy in 19.1% of the sample, although the proportion of the sample in which imputation was used was lower than that used in another study (24.5%) that applied the same methodology 35 . Reported pre-pregnancy weight was also used, which was supported by a strong correlation with measured weight, shown in previous studies on Brazilian pregnant women (r = 0.92) 36 . Finally, different sources of secondary data were used, collected from official records to obtain information regarding the prenatal period.…”
Section: Discussionmentioning
confidence: 81%
“…Stevens-Simon et al [16] and de Oliveira et al [17] found high Pearson correlation coefficients between measured and self-reported maternal prepregnancy weight (r = 0.96 for both). However, a study by Yu et al [18] detected a statistically significant difference of up to 3 kg less for self-reported when compared to estimated weight.…”
Section: Discussionmentioning
confidence: 99%
“…The use of self-reported data has been recommended in conducting large populational studies 23,24 ; however, in this study, these were validated during field work of the original project 25 . For the classification of the pre-gestational nutritional status, according to the BMI, the cutoff points and the classification recommended by the committees: IOM 14,15 and WHO 16 , were used, being this last one with the Z score adapted classification proposed for the food and nutritional surveillance in Brazil 19 .…”
Section: Methodsmentioning
confidence: 99%